Analisis Partisipasi Masyarakat Nahdlatul Ulama Dalam ‎Meingkatkan Pendapatan Dana (Funding) Lazisnu Kota ‎Sumenep - Rahman, Ahmad Taufiqur; Rofiq, Aunur; Wahyuni ‎, Nanik; Muhtadi, Ridan (Ulumuna: Jurnal Studi Keilsman, 2021)
This study aims to answer the question "about how the level of participation of the Nahdlatul Ulama community in the city of Sumenep in increasing the income of funds through the funding program carried out by LAZISNU Sumenep City. The type of research used is descriptive-analytic qualitative research, with the object of research namely, LAZISNU Sumenep City and the Nahdlatul Ulama community scattered in Sumenep City. The data collection method used is semi-structured interview in order to answer the questions addressed. The results of the study show that participation in the annual program is still weak because the NU community who pays zakat, donates, and gives charity is still very small, not yet reaching 25% of the total population of the NU community in Sumenep City. However, participation in the monthly NU association program (lailatu al-ijtima') can be stated to be quite strong because community participation in the program has been proven to encourage an increase in income from the Sumenep City LAZISNU funds. The participation that appears to be very strong is that of all NU administrators in the City of Sumenep because of their form of devotion to Nahdlatul Ulama and their participation in the form of introducing and promoting LAZISNU to the general public, carrying out LAZISNU's strategy of "collecting ZIS assets from the community, and also becoming a donor. under construction The Sumenep City NU MWC Office including the Sumenep City LAZISNU Office.